1989
DOI: 10.1111/j.1651-2227.1989.tb11096.x
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate Enhances Sodium Absorption from Glucose and Glycine Rehydration Solutions.

Abstract: Sodium, potassium and water absorption was studied over the whole length of rat jejunum and ileum by an in vivo marker perfusion technique. The composition of solutions were similar to the oral rehydration solution currently in use for the treatment of acute diarrhoeal diseases. The study shows that bicarbonate and chloride containing glucose or glycine electrolyte solutions induce a significantly greater absorption of sodium, potassium and water compared to those containing chloride only. The study also confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It has been supported by randomized controlled trials as well as meta-analysis that children with vasovagal syncope can benefit from the oral rehydration saline therapy, which can provide a quantified dosage of supplemental water and salt on the basis of the patients’ original diet [ 3 , 18 ]. In addition to the supplementary sodium chloride and fluid volume, other components of oral rehydration saline, such as glucose, can promote the absorption of sodium ions at the small intestine, which may enhance the efficacy of oral rehydration saline [ 24 , 25 ]. Therefore, looking for indicators that can reflect the decrease in blood volume to suggest the oral rehydration saline treatment to the vasovagal syncope patients with low circulating blood volume as the pathogenesis is interesting and potentially useful.…”
Section: Discussionmentioning
confidence: 99%
“…It has been supported by randomized controlled trials as well as meta-analysis that children with vasovagal syncope can benefit from the oral rehydration saline therapy, which can provide a quantified dosage of supplemental water and salt on the basis of the patients’ original diet [ 3 , 18 ]. In addition to the supplementary sodium chloride and fluid volume, other components of oral rehydration saline, such as glucose, can promote the absorption of sodium ions at the small intestine, which may enhance the efficacy of oral rehydration saline [ 24 , 25 ]. Therefore, looking for indicators that can reflect the decrease in blood volume to suggest the oral rehydration saline treatment to the vasovagal syncope patients with low circulating blood volume as the pathogenesis is interesting and potentially useful.…”
Section: Discussionmentioning
confidence: 99%
“…A series of functional studies have indicated that the absorption of Na + and HCO 3 – is closely associated in the small intestinal epithelium. On one hand, HCO 3 – greatly stimulates the absorption of Na + in the small intestine of both human (Fordtran et al, 1968; Turnberg et al, 1970a, b) and rat (Esposito and Csaky, 1977; Humphreys and Chou, 1983; Patra et al, 1989). On the other hand, Na + also stimulates the absorption of HCO 3 – in rat jejunum (Hubel, 1973).…”
Section: Discussionmentioning
confidence: 99%